Amplifying youth voice and cultivating leadership through participatory action research - Rachele Gardner; William M. Snyder; Ayda Zugay (Arizona State University, 2019)
This article presents the story of Youth Hub, a grassroots, neighborhood-based initiative in Boston, Massachusetts, highlighting its use of participatory action research (PAR) to amplify youth voice, cultivate leadership, and promote change. The article includes an explanation of the need from which Youth Hub emerged; a discussion of Youth Hub's use of PAR, including benefits and challenges of the approach; a summary of key research findings; an examination of PAR's usefulness for knowledge creation, including benefits and challenges; and an analysis of youth leadership and ownership in Youth Hub's model, also including benefits and challenges. The article concludes with suggestions for how Youth Hub's approach can be useful for amplifying youth voice and building youth leadership more broadly.